Side Effects and Return of Fertility of Hormonal and Non-Hormonal Contraceptive Acceptors in the Kassi-Kassi Health Center Work Area, Makassar City - Andi Masnilawati Masnilawati; Yusra Taqiah; Nia Karuniawati (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Side effects are an important factor influencing women's contraceptive choices. Concerns such as menstrual disorders, pelvic cramps, excessive bleeding, and delayed return of fertility after discontinuing contraception can negatively impact contraceptive use. This study aimed to examine the side effects and return of fertility among hormonal and non-hormonal contraceptive acceptors in the Kassi Health Center Work Area, Makassar City. An observational analytic study with a cross-sectional design was conducted on 79 contraceptive acceptors selected through purposive sampling. Data were collected through structured interviews using validated questionnaires. Results showed significant associations between menstrual disorders (p=0.029) and changes in body weight (p=0.013) with the type of contraception used. No significant association was found for vaginal discharge (p=0.956), headache/dizziness (p=0.186), and return of fertility (p=0.181) with the contraceptive method. Hormonal contraceptives such as pills were associated with weight gain and headache/dizziness; injections and implants were linked to menstrual disorders, weight changes, vaginal discharge, and headache/dizziness. Non-hormonal contraceptives like IUDs were associated with menstrual disorders and vaginal discharge. These findings highlight the need for personalized contraceptive counseling to consider side effects and fertility expectations in contraceptive decision-making.